Step-by-step explanation:
Given expression is x⁴-kx²+4 =0
x−2 is a factor of the given expression.
So, x=2
Substitute in the equation, we get
2⁴-k(2)²+4
⇒16+4k+4=0
⇒4k=−20
⇒k=−5
Answer:
6/15
Step-by-step explanation:
draw a tree diagram.
the only path with no white is highlighted
multiply them
2/3 x 3/5 = 6/15
Consider this option:
1. if the point (4;6) is the centre of the circle and the point (2;5) is the first endpoint of its diameter, then point (4;6) is the middle point of the diameter (it means that is the middle between the 1st and the 2d endpoints of diameter).
2. using the property described above:
for x of the 2d endpoint of the diameter: x=4*2-2=6;
for y of the 2d endpoint of the diameter: y=6*2-5=7.
answer: (6;7)
Answer:
use The Explicit Formula for the Fibonacci Sequence
Step-by-step explanation: